2020
DOI: 10.1007/s00024-020-02546-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Landslide Modeling: Application to the Scilla 1783 Tsunamigenic Landslide, South Italy

Abstract: In this study, we present a new 2D numerical model, UBO-Inter, able to simulate the motion of a body sliding down a generic surface. Such a body is represented as a mechanical system of a finite number of point masses, where the points can be viewed as the projections on the sliding surface of the centers of mass of the elements which the system is discretized into. The masses are strictly adherent to the surface and interact with the neighbor masses through internal forces. The entire system can be seen as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As a result of field and laboratory surveys of soils, strength properties were determined according to the unconsolidated shear pattern. It was found that the strength properties increase with depth, which is typical of landslide slopes [10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…As a result of field and laboratory surveys of soils, strength properties were determined according to the unconsolidated shear pattern. It was found that the strength properties increase with depth, which is typical of landslide slopes [10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…How to include these factors and their associated probabilities in PTHA is not resolved. While advanced numerical models for landslide dynamics exist (e.g., Tinti et al, 1997;Jop et al, 2006;Savage et al, 2014;Si et al, 2018a;Si et al, 2018b;Kim et al, 2019;Wang et al, 2019;Gallotti and Tinti, 2020), their complexity and variety obfuscate understanding on which models are most suitable to be used. Furthermore, some models (e.g., Savage et al, 2014;Si et al, 2018a;Si et al, 2018b) are presently too comprehensive to be used in PTHA.…”
Section: Limited Constraints On Landslide Dynamics and Materials Behavior (L3)mentioning
confidence: 99%
“…It is a natural calamity that has the capability to have a tremendous socioeconomic impact on a country's population. Natural disasters, as previously mentioned, have the capacity to degrade a purpose of life to the point of wiping out civilisation [2]. At an increased rate of speed, rock, soil, or other debris falls down a steep slope.…”
Section: Introductionmentioning
confidence: 99%